2022
DOI: 10.1029/2021ea002139
|View full text |Cite
|
Sign up to set email alerts
|

An Improved IASI Temperature and Humidity Retrieval Method Based on Double Channel Differences

Abstract: Due to surface emissivity, the retrieval accuracy of hyperspectral infrared temperature and humidity profiles is typically poor in the lower atmosphere. To solve this problem, we use the double channel differences method (DCDM) to retrieve the temperature and humidity profiles of the Infrared Atmospheric Sounding Interferometer (IASI) with different surfaces, zenith angles, and data sources. Results show that DCDM can effectively improve IASI retrieval performance. The root mean square error (RMSE) reductions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Due to the orbit height of polar-orbiting satellites being lower than that of geostationary satellites, the observation accuracy of polar-orbiting satellites is often higher [34,35]. Research on the accuracy of IASI temperature profile products showed that IASI temperature products have good reliability and accuracy [36][37][38]. Therefore, we used IASI temperature as a reference to correct a larger range of GIIRS temperatures.…”
Section: Correction Model Based On the Iasi Level2 Temperature Productmentioning
confidence: 99%
“…Due to the orbit height of polar-orbiting satellites being lower than that of geostationary satellites, the observation accuracy of polar-orbiting satellites is often higher [34,35]. Research on the accuracy of IASI temperature profile products showed that IASI temperature products have good reliability and accuracy [36][37][38]. Therefore, we used IASI temperature as a reference to correct a larger range of GIIRS temperatures.…”
Section: Correction Model Based On the Iasi Level2 Temperature Productmentioning
confidence: 99%